Karakteristik Sosial Ekonomi Petani Agroforestri Pada Areal Hutan Kemasyarakatan (HKm) Sabedo, Kabupaten Sumbawa: Socio-Economic Characteristics of Agroforestry Farmers in the Community Forest Area (HKm) Sabedo, Sumbawa Regency - Yadi Hartono; Wayan Wangiyana; Wahyudi Hadiatma Taqwa; Alia Wartiningsih (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
The socio-economic characteristics of communities living near forests are variables that need to be taken into account when formulating forest management objectives. HKm Sabedo is one of nine HKms in Sumbawa that are managed using an agroforestry system. Research objectives: 1) to describe agroforestry practices in HKm Sabedo; 2) to identify the socio-economic characteristics of farmer managers; and 3) to estimate farmers' income equivalent to rice. The method used is a descriptive method. The social characteristics measured are: age, family members, education level, health level, and length of stay. Economic characteristics: land area owned, HKm cultivated land area, and farmers' income from HKm land. The results of the study indicate that the agroforestry pattern applied is a combination of MPTs, plantation crops, and seasonal crops. There are 22 types cultivated, and only 8 are traded. The average age of farmers is 34 years old, with an average of 2 dependents per household, and an educational background of junior high school to senior high school. Health status is classified as good, and 88.58% of farmers have been members of their community for over 31 years. The average land area under HKm is 1.3 hectares, and the average land ownership is over 0.5 hectares, placing them in the category of medium-sized farmers. The average income from HKm land is Rp. 15,643,974 per year, equivalent to 1,141 kg of rice (assuming an average rice price of Rp. 13,716). With an average of 2 family members, this rice-equivalent income falls within the non-poor criteria